(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The present paper concerns the logistic aspect of human resource management andparticularly the logistics of employees. Logistic methods of supporting managers maybe applied not only in the logistics itself(in traditional sense of this word) ,eg thelogistics of supplies ,but also play its role in the process of selecting employees. Thesemethods assure that the logistics of employees selection localizes itself in the universeof time, costs and quality(as three independent parameters) and besides point to theapplication of considerable logistics resources in their realization.